2019
DOI: 10.3390/wevj10020017
|View full text |Cite
|
Sign up to set email alerts
|

Battery Life Enhancement in a Hybrid Electrical Energy Storage System Using a Multi-Source Inverter

Abstract: This paper introduces a new topology using a multi-source inverter with the intention of reducing the battery current and weight, while enhancing the battery life and increasing the driving range for plug-in electric vehicles, with the combination of a battery and an ultracapacitor (UC) as storage devices. The proposed topology interconnects the UC and battery directly to the three-phase load with a single-stage conversion using an inverter. The battery life is considerably reduced due to excess (peak) current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 28 publications
0
6
0
Order By: Relevance
“…The SHEB uses the ESS of the battery and UC connected in parallel. The battery usually demonstrates an advantage in energy density over the UC; conversely, the power density of the UC is more advanced than the battery [2,32]. UCs are well known for their high capacitance and semi-permanent lifetime [33].…”
Section: Ess Modelingmentioning
confidence: 99%
“…The SHEB uses the ESS of the battery and UC connected in parallel. The battery usually demonstrates an advantage in energy density over the UC; conversely, the power density of the UC is more advanced than the battery [2,32]. UCs are well known for their high capacitance and semi-permanent lifetime [33].…”
Section: Ess Modelingmentioning
confidence: 99%
“…The proposed EMS allows to manage the powers between the first and the second fictitious machines using the power ratio as shown in (17). In addition, in each fictitious machine, to control the powers of the battery and supercapacitors, lowpass filters are applied as shown in Fig.…”
Section: B Proposed Energy Management Strategymentioning
confidence: 99%
“…Supercapacitors can be used in accelerations and decelerations (short-term power demand) while the battery is used for operations at constant speeds. The EVs driven by wye-connected winding 3-phase machines fed by single inverter, using batteries and supercapacitors, have been investigated in [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, there are some application and evaluation in the literature about alternative-fuel vehicle technology (Oztaysi et al 2017;Mukherjee 2017;Vaughan et al 2018;Sehatpour et al 2017;Yavuz et al 2015;Li et al 2019). Besides, various applications and research interests in the EV field such as environmental impact assessment (Choma, Ugaya 2017; Ensslen et al 2017;Nordelöf et al 2014), environmental life cycle assessment (Ercan et al 2015;Zhang et al 2018Zhang et al , 2019, charging technologies and battery technologies (Shareef et al 2016;Fotouhi et al 2016;Song et al 2018;Mahadik, Vadirajacharya 2019;Chiranjeevi et al 2020), charging infrastructure and location planning of charging stations (Andrenacci et al 2016;Xu et al 2016;Kong et al 2017;Guo, Zhao 2015;Awasthi et al 2017;Lin et al 2020) are found in the scientific literature.…”
Section: Introductionmentioning
confidence: 99%